Role of labor mobility and competition in economic development - Tan, Boon Yee (2015)
This dissertation consists of two independent essays, both of which are empirical assessments of economic impacts of foreign direct investment. The first essay tests the role labor mobility play in mediating the growth-effect of FDI ,A panel of 120 countries plus Hong Kong across 13 years from 2000 to 2012 is analyzed using GMM panel estimator. The results show that FDI has no direct impact on output growth, but the positive and significant interaction between FDI and labor mobility show that labor movement facilitate the externalities gained from FDI. Domestic investment and population growth are both very significant in the growth regression, with positive and negative effect respectively. The second essay investigates the relationship between FDI inflow and R&D expenditure conditional on product market competition level in a cross country setting. Generalized Method of Moments (GMM) estimator is used to estimate the relationship among the key variables. A sample data consists of 61 countries spanning from 2000 to 2011 is being analyzed in this study. This study finds that FDI has a positive direct effect on R&D, but its effect manifest negatively conditional on competition level.However, the positive direct effect of FDI on R&D is not very robust. The finding contradicts conventional wisdom regarding merits of competition and provides evidence on how competition undermines the effect of FDI on domestic R&D.